Analisis Pengaruh Kebijakan Birokrasi Terhadap Efektivitas Pelayanan Publik Di Lampung - Berchah Pitoewas; Abdul Halim; Martines Sabiliun Muttaqina; Elza Zeriana; Ferdiansyah Ferdiansyah; Riskiya Dina Paramita; Ratna Wulandari; Bagus Permana; Rifdah Assyifa (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of bureaucratic policy on the effectiveness of public services in Lampung Province through a literature review approach. In the context of modern governance, bureaucracy plays a vital role in delivering efficient, transparent, and accountable public services. A review of various scholarly sources reveals that well-designed bureaucratic policies can significantly enhance service quality, particularly through organizational reform, digital service implementation, and strengthening the capacity of civil servants. However, the literature also highlights persistent challenges, such as overlapping regulations, low accountability, and resistance to change, which hinder effective policy implementation at the regional level. In the case of Lampung, the effectiveness of public services is largely determined by how consistently and adaptively bureaucratic policies are applied to meet public needs. Therefore, this study recommends improving evidence-based bureaucratic policies, continuous capacity-building programs for civil servants, and stronger performance evaluation systems as strategic efforts to enhance public service delivery.